2021
DOI: 10.1186/s12936-021-03672-8
|View full text |Cite
|
Sign up to set email alerts
|

Seven decades towards malaria elimination in Yunnan, China

Abstract: Background Yunnan Province was considered the most difficult place in China for malaria elimination because of its complex malaria epidemiology, heterogeneous ecological features, relatively modest economic development, and long, porous border with three malaria endemic countries: Lao People’s Democratic Republic, Myanmar, and Viet Nam. Methods Academic publications and grey literature relevant to malaria elimination in Yunnan covering the period f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…While PPQ resistance was documented clinically in Cambodia in 2014, reports dating back to the 1980s suggest resistance previously emerged in Yunnan Province, China, when PPQ was used as a monotherapy to treat CQ-resistant malaria [36][37][38]. This region borders Myanmar, Laos and Vietnam and was the most difficult region to control malaria transmission in China [39]. We hypothesized that mutations in PfCRT may explain the early PPQ resistance in Yunnan Province and that investigating PPQ-resistant isoforms from that region could provide important evolutionary clues when compared to the structure and function of the currently circulating isoforms.…”
Section: Introductionmentioning
confidence: 99%
“…While PPQ resistance was documented clinically in Cambodia in 2014, reports dating back to the 1980s suggest resistance previously emerged in Yunnan Province, China, when PPQ was used as a monotherapy to treat CQ-resistant malaria [36][37][38]. This region borders Myanmar, Laos and Vietnam and was the most difficult region to control malaria transmission in China [39]. We hypothesized that mutations in PfCRT may explain the early PPQ resistance in Yunnan Province and that investigating PPQ-resistant isoforms from that region could provide important evolutionary clues when compared to the structure and function of the currently circulating isoforms.…”
Section: Introductionmentioning
confidence: 99%
“…Our study detected 6 asymptomatic infections, accounting for 5.6% of the migrant population from Vietnam, in this study. Unlike the China-Myanmar border, which poses a substantial challenge for malaria elimination in Yunnan Province due to the high prevalence of P. vivax and P. falciparum in northern Myanmar [ 14 , 15 ], the China-Vietnam border seems to be “forgotten” in terms of malaria prevention because of the low incidence of malaria in northern Vietnam. The incidence rates in two border counties on the China-Myanmar border, Jingxi and Longzhou counties, decreased to 4.0 and 4.27 per 100,000 in the late 20th century, respectively, and no indigenous cases occurred during the early 21st century [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ndings in our study have revealed that 6 asymptomatic infections detected, accounting for 5.6% of all migrant population from Vietnam. Unlikely the China-Myanmar border, which may pose great challenge for malaria elimination to Yunnan Province due to the high prevalence of P. vivax and P. falciparum in northern Myanmar [11,12], malaria in the China-Vietnam border seems a "forgotten disease" because of the low incidence in northern Vietnam. Hai Phong, located in the northern Vietnam, the average positive predictive values was 0.10% in 2010-2014 [13].…”
Section: Discussionmentioning
confidence: 99%